Dynamics of Storage Materials in Cotyledon During Cocoa Seed Germination - Sakiroh Sakiroh; Taryono Taryono; Setyastuti Purwanti (Jurnal Ilmu Pertanian, 2018)
Degradation of carbohydrate, protein and lipid food reserves occurs in the seed germination process to produce energy for germination and further growing. This study aimed to determine dynamics the content of protein, carbohydrates, and lipid in cotyledon of seed clon i.e. Sca 6, RCC 70, RCC 71 and KKM 22 during germination. The experiment used completely randomized design consisted of four replications with 4 treatments. In each cocoa germination phases i.e. before germination, phase II (bend/curved phase), cotyledon emergence, leaves emergence and fall of cotyledon from the sprouts. This observation were water content, ash content, lipid, soluble protein, total protein and carbohydrate content. The results of the experiment showed that during germination, there was an increase of water content in cotyledon from the bend phase to the leaf emergence and decrease in the phase of fall of cotyledon The highest water content was observed in the leaf emergence phase as high as 69.42%. The content of ash content, dissolved protein, total protein and carbohydrates in cotyledon fluctuated during the bend phase until the leaf emergence and increased in the phase of fal of cotyledon. ipid content has decreased from the bend phase until the fall of cotyledons. Carbohydrate levels have increased from the bend phase to the fall of cotyledons. The speed of degradation procces of seed stored material (water, lipid, protein and carbohydrate content) during germination is affected by differences in seed clones. The Scavina 6 and KKM 22 clones entered the bend phase and the realease of cotyledon.